1996
DOI: 10.1007/bf02265258
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in the regulation of plasma high density lipoprotein cholesterol by genetic and environmental factors

Abstract: Association between high density lipoprotein (HDL) cholesterol concentration and restriction fragment length polymorphisms at the cholesteryl ester transfer protein (CETP) gene locus was studied in a random population-based cohort of 526 Caucasian subjects (259 men, mean age 50.9 years, and 267 women, mean age 51.8 years). HDL cholesterol concentration was adjusted for age, body mass index, alcohol consumption, smoking and plasma triglyceride and low density lipoprotein cholesterol levels. In females, the HDL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 28 publications
7
66
0
Order By: Relevance
“…[3][4][5]8,[35][36][37] In some reports, the association was seen only in subgroups, such as ex-and nonsmokers, 38 or in women, but not in men. 39 Alhough we could not replicate the association of an increased baseline HDL-C in the presence of the mutant B2 allele of SNP4, the strong stepwise decrease in CETP mass and activity associated with the number of B2 alleles of SNP4 clearly underlines such an expected effect on HDL-C. With respect to SNP 7 (A373P) and SNP8 (R451Q), the Copenhagen City Heart Study found a decrease in HDL-C and ApoA1 in carriers of the mutant allele, both in men and women. 11 Despite the low frequency of these mutant alleles, we also observed a significant decrease in HDL-C associated with the SNP7 (A373P) CETP polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5]8,[35][36][37] In some reports, the association was seen only in subgroups, such as ex-and nonsmokers, 38 or in women, but not in men. 39 Alhough we could not replicate the association of an increased baseline HDL-C in the presence of the mutant B2 allele of SNP4, the strong stepwise decrease in CETP mass and activity associated with the number of B2 alleles of SNP4 clearly underlines such an expected effect on HDL-C. With respect to SNP 7 (A373P) and SNP8 (R451Q), the Copenhagen City Heart Study found a decrease in HDL-C and ApoA1 in carriers of the mutant allele, both in men and women. 11 Despite the low frequency of these mutant alleles, we also observed a significant decrease in HDL-C associated with the SNP7 (A373P) CETP polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 9 population-based studies qualified for inclusion: 4 prospective studies: the Framingham Offspring Study (FOS), 20 the Physicians' Health Study (PHS), 21 the Northwick Park Heart Study (NPHS), 22 and the Reykjavik study; 23 and 5 cross-sectional studies: the European Atherosclerosis Research Study (EARS), 24 Etude Cas-Témoins de l'Infarctus du Myocarde (ECTIM), 15,25,26 the Oulu Project Elucidating Risk of Atherosclerosis (OPERA), 11,27 a study performed by Arca et al, 28 and one performed by Corella et al 29 Databases with individual patient data were obtained from all studies except for the FOS and the study performed by Corella et al 20,29 ; thus these 2 studies were not included. We identified 3 randomized, double-blind, placebo-controlled trials of pravastatin treatment wherein a subanalysis had been performed on the role of the TaqIB polymorphism: the Regression Growth Evaluation Statin Study (REGRESS), 7 the Cholesterol And Recurrent Events trial (CARE), 9 and the West of Scotland Coronary Prevention Study (WOSCOPS).…”
Section: Resultsmentioning
confidence: 99%
“…We investigated whether our pooled dataset provided any evidence for the published interactions between TaqIB genotype and sex, 11,12 smoking, 8,13 BMI, 13,14 and use of alcohol. 15 The present meta-analysis provides some evidence that interactions exist for both sex and smoking (Pϭ0.02 for each), such that the effect of TaqIB genotype on HDL-C levels was attenuated among men and among smokers.…”
Section: Effect Modification By Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements of plasma triglyceride concentrations and very-low-density lipoprotein (VLDL), high-density lipoprotein (HDL) and low-density lipoprotein (LDL) cholesterol levels have been described in detail elsewhere (25). All the subjects volunteered for the study, which was approved by the Ethical Committee of the University of Oulu.…”
Section: Subjectsmentioning
confidence: 99%